2021
DOI: 10.1002/ueg2.12097
|View full text |Cite
|
Sign up to set email alerts
|

The gastrointestinal tract in hunger and satiety signalling

Abstract: Background: Different peripheral pathways are implicated in the regulation of the food ingestion-digestion cycle.Methods: Narrative review on gastrointestinal mechanisms involved in satiety and hunger signalling.Results: Combined mechano-and chemoreceptors, peripherally released peptide hormones and neural pathways provide feedback to the brain to determine sensations of hunger (increase energy intake) or satiation (cessation of energy intake) and regulate the human metabolism. The gastric accommodation reflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 59 publications
1
48
0
1
Order By: Relevance
“…In FD, increased sensitivity to capsaicin administration has been reported, suggesting hypersensitivity to TRPV1 receptor activation ( 18 ). In healthy subjects, bitter tastants inhibit the release of motilin and ghrelin and suppress the occurrence of gastric phase 3, which is associated with decreased hunger sensations ( 19 , 20 ), but alterations in DGBI have not been studied to date. Low- or non-caloric sweeteners such as erythritol and xylitol do not alter plasma glucose or insulin levels, can stimulate the secretion of gut peptides such as CCK, GLP-1 and PYY, and slow down gastric emptying ( 21 , 22 ).…”
Section: Nutrient Sensing and Tastingmentioning
confidence: 99%
“…In FD, increased sensitivity to capsaicin administration has been reported, suggesting hypersensitivity to TRPV1 receptor activation ( 18 ). In healthy subjects, bitter tastants inhibit the release of motilin and ghrelin and suppress the occurrence of gastric phase 3, which is associated with decreased hunger sensations ( 19 , 20 ), but alterations in DGBI have not been studied to date. Low- or non-caloric sweeteners such as erythritol and xylitol do not alter plasma glucose or insulin levels, can stimulate the secretion of gut peptides such as CCK, GLP-1 and PYY, and slow down gastric emptying ( 21 , 22 ).…”
Section: Nutrient Sensing and Tastingmentioning
confidence: 99%
“…This process of active relaxation is mediated by different parasympathetic reflex pathways, which lead to an increased NO release in humans [ 62 ]. Even if accommodation is usually considered as a mechanism which allows the stomach to prevent a rise in intragastric pressure during food intake [ 63 ], studies in humans have reported that ingestion of nutrients evokes an initial drop in the intragastric pressure, followed by a gradual recovery [ 64 ]. Gastric accommodation is based on fundal relaxation and studies in humans have shown such relaxation to be dependent upon NO [ 65 , 66 ].…”
Section: No In Gastric Motility and Dysmotilitymentioning
confidence: 99%
“…The latter triggers stretch and tension, so stimulating mechanosensitive receptors which, in turn, communicate their information through the activation of the vagal afferent nervous fibers. These latter send signals to the hypothalamic regions involved in the regulation of food intake, through the interposition of the nucleus of the tractus solitarius [ 63 ]. Thus, besides anorexigenic gut hormones, such as cholecystokinin and glucagon-like peptide-1, which cause gastric distension and slow down emptying, satiety induced by gastric distension can also be regulated by some adipocyte-released peptides [ 63 , 73 ].…”
Section: No In Gastric Motility and Dysmotilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A reflection of this is the increasing followers' number of the UEG Journal Twitter account, reaching almost 6000 over barely 3 years. In 2021, we put emphasis on visual graphic content presentation in SoMe, as a distinction for 29 manuscripts published in UEG journal, covering the various GI fields including inflammatory bowel diseases, 12,13 endoscopy, 14 pancreas, 15,16 obesity, 17 gut, 18 GI tract physiology, 19 and the European guidelines. 1,2 We believe that an eye-friendly summary presentation form of published papers will beef up the UEG Journal overview and amplify the authors' effort.…”
mentioning
confidence: 99%